Evolutionary views on entrepreneurial processes: Managerial and policy implications - Karl Wennberg; Frédéric Delmar (Research Institute of Industrial Economics (IFN), 2011)
In this paper we outline an evolutionary framework of entrepreneurial processes where by firms are started, grow, and exit from the market. We explain the important of such a framework in explaining both what contextual factor affects entrepreneurial processes and in explaining the distinction and interaction between self-employment and high-potential entrepreneurship. We highlight the implications from prior empirical work using this evolutionary framework for management and policy making: Three broad implications relevant for managers and entrepreneurs interested in understanding how they can leverage their chances to position their firms as ripe for growth, and six detailed implications relevant for policy makers interested in understanding and affecting the structural conditions where by entrepreneurship can lead to enhanced growth and job creation.
Keywords: 330